Where Is My Crop? Data-Driven Initiatives to Support Integrated Multi-Stakeholder Agricultural Decisions - Andrade, Robert; Urioste, Sergio; Rivera, Tatiana; Schiek, Benjamin; Nyakundi, Fridah; Vergara, Jose; Mwanzia, Leroy; Loaiza, Katherine; Gonzalez, Carolina (Frontiers in Sustainable Food Systems, 2021)
Globally, there has been an explosion of digital data across all sectors of society, and agriculture is no exception. With such a deluge of data available, it has become essential to create solutions that organize, analyze, and visualize these data to gain actionable insights. These insights can guide smallholder farmers to make better, faster, and smarter decisions that lead to transformative actions for their production systems. Currently, several initiatives are ongoing for rice, cassava, beans, plantain and banana, and tropical forages to provide such insights based on open-access data belonging to various international and national institutions. The data include information on production, prices, policies, breeding, agronomy, and socioeconomic variables of interest. These Crop Observatories are expected to become a lighthouse that attracts stakeholders to avoid “not see the forest for the trees” and to advance research and strengthen crop economic systems for smallholders. There is a need to step further from the trees, see the forest, and consider the big picture. Properly harmonizing and managing different datasets to generate insightful analyses have enormous power and encourage collaboration to generate new research questions. The recently launched initiative, the Rice Observatory (www.riceobservatory.org), responds to the requests expressed by various rice-related institutions in Latin America that wanted to understand and improve regional competitiveness, emphasizing cost efficiency gains and natural resource sustainability. Meanwhile, the initiative about to be launched, the Cassava Lighthouse (www.cassavalighthouse.org), has global scope for the cassava economy to position and strengthen the global cassava research agenda and provide updated price information for cassava producers in Asia. Other Crop Observatories are in the pipeline (e.g., for common beans, banana and plantain, and tropical forages). Our teams expect to mature and integrate more partners to participate in the initiative, genuinely becoming a shining light in the global context of agriculture.